Dual energy computed tomography analysis in cancer patients: What factors affect iodine concentration in contrast enhanced studies?. Issue 120 (November 2019) - Corrias, Giuseppe; Sawan, Peter; Mahmood, Usman; Zheng, Junting; Capanu, Marinela; Salvatore, Marco; Spinato, Giacomo; Saba, Luca; Mannelli, Lorenzo
Highlights: Iodine concentration in the aorta increased with higher rate of injection. No association was found with iodine concentration within the aorta and paraspinal muscles. Iodine concentration in the aorta was higher in lower body mass index. Abstract: Purpose: The aim of the study is to explore the patient's and scan's parameters that affect the iodine concentration in the abdomen using dual energy computed tomography (DECT) in an oncologic population. Method: This is a retrospective study with consecutive patients with different cancers who underwent a single-source DECT (ssDECT) examinations at our institution between years 2015 and 2017. On axial IODINE images, the radiologist manually drew a circular ROI along the inner contour of the aorta. Mean iodine concentration and ROI areas were recorded. Body mass index for every patient was recorded. Descriptive statistics were summarized for iodine concentration and patient/scan characteristics. Linear regression was used to examine associations between iodine concentration in aorta and studied characteristics. Statistical significance was set at a p value < 0.05. Results: The univariate analysis, showed a statistically significant association between iodine concentration within the aorta and the area of ROI (Estimated Coefficient β: −0.013), the rate of injection (Estimated Coefficient β: 2.09), the acquisition time (Estimated Coefficient β: −0.195). In multivariable analysis iodine concentration in the aorta increased with higher rate of injection (4 ml/sec), smaller ROI area and lower BMI. Conclusion: Our results showed how iodine concentration is highly dependent on some intrinsic and extrinsic parameters of the examination. These parameters should be taken into account since lower concentration of iodine decrease contrast-to-noise ratio, and in longitudinal follow up studies, they would affect iodine quantitive assessments in cancer patients with frequent chemotherapy-induced variations in BMI and cardiac function.